The Influence of Competence in Utilizing Learning Media, Managing Class, and Diagnosis of Students' Learning Difficulties on Teaching Performance of Visual Communication Design Teachers of Vocational Schools in Yogyakarta - Djarot Wahyu Sasongko; Tri Kuat; Muhammad Sayuti (Universitas Ahmad Dahlan, 2023)
This study aims to analyze the influence; teacher competence in utilizing instructional media, teacher competence in managing classes, teacher competence in diagnosing student learning difficulties and analyzing the influence of teacher competence simultaneously on teaching performance of Visual Communication Design teachers at vocational school (SMK) in Yogyakarta, namely at SMK Negeri 3 Kasihan Bantul, SMK Negeri 5 Yogyakarta , SMK Negeri 2 Sewon Bantul, SMK Koperasi Yogyakarta and SMK Muhammadiyah 2 Yogyakarta. Research using quantitative methods. The technique of collecting data is done by questionnaire. Data processing analysis by means of validity test, reliability test. Statistical prerequisite tests were carried out through the normality test, linearity test, multicollinearity test and heteroscedasticity test. Data analysis was carried out through correlation tests, coefficient of determination tests and F tests. The results showed that; 1) there are positive and significant effects of all the variables teacher competence: in utilizing instructional media, in managing the class, and in diagnosing student learning difficulties on teachers teaching performance of Visual Communication Design teachers at vocational school (SMK) in Yogyakarta. It is hoped that teachers will always be able to develop themselves, maintain and improve their teaching performance by increasing their competence.